Association between temporomandibular disorder symptoms and oral health-related quality of life among adults: the mediating role of teeth-related psychosocial factors - Su-Kyung Han; Kyeung-Ae Jang (Journal of Korean Society of Dental Hygiene, 2026)
Objectives: This study aimed to investigate the association between temporomandibular disorder (TMD) symptoms and oral health-related quality of life (OHRQoL) and examine the potential mediating role of teeth-related psychosocial factors among adults. Methods: A self-administered questionnaire survey was conducted with 201 adults recruited by convenience sampling in Busan, South Korea. Data were analyzed using IBM SPSS Statistics version 29.0 and Hayes’ PROCESS macro. Frequency analyses, t-tests, one-way analysis of variance (ANOVA), correlation analyses, and mediation analysis were performed, with the mediation analysis adjusted for educational level, smoking status, and drinking frequency. Results: TMD symptoms and teeth-related psychosocial factors differed significantly with smoking status and drinking frequency, whereas OHRQoL differed significantly with educational level. TMD symptoms were negatively correlated with teeth-related psychosocial factors and OHRQoL, whereas teeth-related psychosocial factors were positively correlated with OHRQoL. After adjustment for educational level, smoking status, and drinking frequency, TMD symptoms were significantly associated with OHRQoL (direct effect: B = −0.578, p < 0.001). The indirect association between TMD symptoms and OHRQoL through teeth-related psychosocial factors was also statistically significant (indirect effect = −0.098, 95% bootstrap CI: −0.175 to −0.040). Conclusions: TMD symptoms were directly associated with OHRQoL and indirectly associated through teeth-related psychosocial factors. Integrated approaches that address TMD symptom management and teeth-related psychosocial factors may help improve OHRQoL.